KONFLIK MUSLIM-HINDU DI INDIA KONTEMPORER (MASA PEMERINTAHAN NARENDRA MODI) - Fuad Reza Pahlevi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research examines the Muslim-Hindu Conflict in Contemporary India (Narendra Modi's Reign) The Sangh Parivar is a nationalist Hindu organization consisting of the Vishva Hindu Parishad, Bajrang Dal, Rashtriya Swayamsevak Sangh (RSS), and Bharatiya Janata Party (BJP). The group seeks to establish Hindu Rashtra, an Indian theocracy that adheres to Hindu principles. However, the Sangh Parivar is not a purely religious organization. The construction of India as a Hindu state is the result of the application of the ideology of Hindutva, which is the ideology of modern Indian society derived from Hinduism. The method used for this study is qualitative research and literature study, this study explores how Hindutva ideology and the Rashtriya Swayamsevak Sangh (RSS). Based on the theory put forward by Appleby called the term "strong religion", which argues that religion with a fundamentalist nature can be a deadly force. The results show that the conflict that occurred in India is a religious conflict that is ridden by political interests. This finding emphasizes the importance of understanding the nature of religion in everyday life.